Exploring the Transformative Potential of Education - Baniwal, Vikas; Bhatia, Aakanksha; Sawhney, Amanpreet K; Sandhu, Manika; Mahajan, Vanshika (Voices of Teachers and Teacher Educators, 2019)
The present paper attempts to explore the transformative potential of education, not just for personal transformation, but also social change. However, since every attempt at transformation is not without resistance, thus, this paper also discusses a few of the struggles and road blocks that one faces on the road to transformation. The paper builds on the experiences of pupil-teachers of the Department of Education at the University of Delhi, through narratives of their significant experiences during their School Experience Program. These experiences were discussed with the teacher-educator to reflect on the possible responses and their theoretical justifications. The paper, thus, articulates questions that arose in the young minds of the pupil-teachers and some of the directions that they found to answer these questions.